Survival probability of large rapidity gaps in a QCD model with a dynamical infrared mass scale - Luna, E. G. S. (Elsevier B.V., 2006)
We compute the survival probability {vertical bar S vertical bar(2)} of large rapidity gaps (LRG) in a QCD based eikonal model with a dynamical gluon mass, where this dynamical infrared mass scale represents the onset of nonperturbative contributions to the diffractive hadron-hadron scattering. Since rapidity gaps can occur in the case of Higgs boson production via fusion of electroweak bosons, we focus on WW -> H fusion processes and show that the resulting {vertical bar S vertical bar(2)} decreases with the increase of the energy of the incoming hadrons; in line with the available experimental data for LRG. We obtain {vertical bar S vertical bar(2)} = 27.6 +/- 7.8% (18.2 +/- 17.0%) at Tevatron (CERN-LHC) energy for a dynamical gluon mass m(g) = 400 MeV. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: diffractive Higgs production; rapidity gaps; QCD eikonal models